Assessment of the Preventive Effect Against Diabetic Cardiomyopathy of FGF1-Loaded Nanoliposomes Combined With Microbubble Cavitation by Ultrasound - Zheng, Lei; Shen, Chuan-Li; Li, Jian-Min; Ma, Yu-Lei; Yan, Ning; Tian, Xin-Qiao; Zhao, Ying-Zheng (Frontiers in Pharmacology, 2020)
Acidic fibroblast growth factor (FGF1) has great potential in preventing diabetic cardiomyopathy. This study aimed to evaluate the preventive effect of FGF1-loaded nanoliposomes (FGF1-nlip) combined with ultrasound-targeted microbubble destruction (UTMD) on diabetic cardiomyopathy (DCM) using ultrasound examination. Nanoliposomes encapsulating FGF1 were prepared by reverse phase evaporation. DM model rats were established by intraperitoneal injection of streptozotocin (STZ), and different forms of FGF1 (FGF1 solution, FGF1-nlip, and FGF1-nlip+UTMD) were used for a 12-week intervention. According to the transthoracic echocardiography and velocity vector imaging (VVI) indexes, the LVEF, LVFS, and VVI indexes (Vs, Sr, SRr) in the FGF1-nlip+UTMD group were significantly higher than those in the DM model group and other FGF1 intervention groups. From the real-time myocardial contrast echocardiography (RT-MCE) indexes, the FGF1-nlip+UTMD group A and A×β showed signiﬁcant differences from the DM model group and other FGF1 intervention groups. Cardiac catheter haemodynamic testing, CD31 immunohistochemical staining, and electron microscopy also confirmed the same conclusion. These results confirmed that the abnormalities, including myocardial dysfunction and perfusion impairment, could be suppressed to different extents by the twice weekly FGF1 treatments for 12 consecutive weeks (free FGF1, FGF1-nlip, and FGF1-nlip+UTMD), with the strongest improvements observed in the FGF1-nlip+UTMD group. In conclusion, the VVI and RT-MCE techniques can detect left ventricular systolic function and perfusion changes in DM rats, providing a more effective experimental basis for the early detection and treatment evaluation of DCM, which is of great significance for the prevention of DCM.